Fundamental Liberties In The Malayan Constitution And The Search For A Balance, 1956–1957 - Fernando, Joseph M. (Penerbit Universiti Sains Malaysia (USM Press), 2017)
This article examines the framing of the section on fundamental liberties in the 1957 Malayan constitution and analyses the underlying intentions and concerns of the framers and the various influences on the drafting process through an investigation of the primary constitutional documents. The section on fundamental liberties sought to provide for the growth of a democratic way of life in independent Malaya (now Malaysia). The Reid Commission, which framed the initial draft of the constitution, provided strong constitutional safeguards for basic fundamental liberties and rights such as personal liberty; equality of citizenship; freedom of movement, speech, assembly and association; freedom of religion and rights in respect of education and private property. Such provisions in most post-war Commonwealth constitutions drew little controversy. The complex multiracial and multireligious Malayan environment, however, required the framers to balance the competing demands of the various communities, on one hand, and the powers of the state over the citizens, on the other.